Perencanaan Pensiun Pekerja Swasta: Pentingnya Financial Literacy dan Saving Behavior - Santoso, Nicholas Adi; Pertiwi, Dewi; Astuti, Dewi (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2022)
This study aims to see the influence of financial literacy and saving behavior towards retirement planning of private-sector workers in Blitar. This study uses a quantitative method using a questionnaire method. The sample of the data studied are private-sector employee who have worked at least 1-2 years in several company totaling 100 people. Data obtained by using a questionnaire to the respondents. The data analysis technique used is SEM analysis with Partial Least Square (PLS). The results of the analysis show that financial literacy has a significant effect on retirement planning for private-sector workers in Blitar and saving behavior has a significant effect on retirement planning for private-sector workers in Blitar district.